Heavy metal profiling of hair and nail samples among the traffic police personnel - Abd Hamid, Abdul Alif (2017)
Heavy metals are formed in the earth and became concentrated as a result of human caused activities. Sources of heavy metals are generally from mining, industrial wastes, fertilisers, paint, and vehicle emissions. Vehicle emissions are major source of airborne contaminants including arsenic, cadmium, cobalt, nickels, lead, antimony, zinc, platinum and others. Heavy metals come into plant, animal, and human tissues through inhalation, diet, absorption via skin contact and human handling. Heavy metals can accumulate and traced in biological matrices such as hair and nail as they are hard to metabolise and directly produce the toxicity effects. This research was a comparison study which focused on the evaluation of the heavy metals exposure concentrations among outdoor traffic police personnel as compared to the indoor traffic personnel. This study involved 86 respondents from traffic police personnel of Jalan Tun H. S. Lee, Police Traffic Station. Questionnaires regarding the underlying factors of exposure were distributed to collect data as well as demographics facts. The samples of hair and nail from respondents were collected. The hair and nail samples were pre-treated using microwave assisted acid digestion method. Samples then were analysed using Inductively Coupled Plasma-mass Spectrometry (ICP-MS) to measure the concentrations of heavy metals namely arsenic (As), cadmium (Cd), lead (Pb), nickel (Ni) and zinc (Zn). The mean concentrations of selected metals in hair and nail samples from outdoor with regards indoor traffic police personnel were determined and compared. The results indicated that there was no significant difference between the mean concentrations of heavy metals in hair and nail samples of outdoor and indoor traffic police personnel. This was true except for As and Zn concentration in hair as well as Cd and Ni in nails (p < 0.05). However, it was demonstrated that there was no correlation between occupational exposure with the mean concentrations of heavy metals of interest. A paired sample t-test showed that the Zn concentration was significantly higher in hair than in the nail sample (p<0.05).Multifactorial ANOVA test demonstrated that the risk or underlying factors such as group, age, working experience, working hours per shift and lifestyle factors such as electronic smoke exposure have a significant impact on the mean concentration of As. Meanwhile,years of working experience, shisha and chemical exposure have a significant influence on the mean concentration of Pb. The mean of Ni was influenced by gender, working experience and exposure of petroleum. Group, gender and working hours per week have a significant influence on the mean concentration of Zn. Results from this study can be used as a baseline data for relevant authorities to develop policies and taking necessary intervention to address the risks of heavy metals exposure as well as to create awareness regarding these issues for public health.